Safety and durability of AGT103-T autologous T cell therapy for HIV infection in a Phase 1 trial - Muvarak, Nidal; Li, Haishan; Lahusen, Tyler; Galvin, Jeffrey A.; Kumar, Princy N.; Pauza, C. David; Bordon, José (Frontiers in Medicine, 2022)
The cell and gene therapy product AGT103-T was designed to restore the Gag-specific CD4+ T cell response in persons with chronic HIV disease who are receiving antiretroviral therapy [1]. This autologous, genetically engineered cell product is under investigation in a Phase I clinical trial (NCT03215004). Trial participants were conditioned with cyclophosphamide approximately 1 week before receiving a one-time low (<109 genetically modified CD4+ T cells) or high (>109 genetically modified CD4+ T cells) dose of AGT103-T, delivering between 2 and 21 million genetically modified cells per kilogram (kg) body weight. There were no serious adverse events (SAEs) and all adverse events (AEs) were mild. Genetically modified AGT103-T cells were still detected in most of the participant blood samples collected six months after infusion, which was the last scheduled monitoring visit. Peripheral blood mononuclear cells (PBMC) collected after cell product infusion were tested to determine the magnitude of Gag-specific T cells as a measure of objective responses to therapy. Gag-specific CD4+ T cells were detected in all treated individuals and were substantially increased by 9 to 300-fold compared to baseline at 14 days after cell product infusion. Gag-specific CD8+ T cells were increased by 1.7 to 10-fold relative to baseline by 28 days after cell product infusion. Increased levels of Gag-specific CD4+ T cells were still detected ( 2 to 70-fold higher relative to baseline) during 3 to 6 months after infusion. AGT103-T at low or high doses was safe and effective for improving host T cell immunity to HIV. Further studies, including antiretroviral treatment interruption, are warranted to evaluate the product’s efficacy in HIV disease.